When you trap a tiger [large type] - Keller, Tae (Thorndike press large print striving reader collection, 2020)
"When Lily and her family move in with her sick grandmother, a magical tiger straight out of her halmoni's Korean folktales arrives. The tiger offers Lily a deal- if Lily will open her grandmother's star jars and return what she stole, the tiger will heal her grandmother. But deals with tigers are never what they seem! With the help of her sister and her new friend Ricky, Lily must find her voice . . . and the courage to face a tiger. Tae Keller, the award-winning author of The Science of Breakable Things, shares a sparkling tale about the power of stories and the magic of family.Think Walk Two Moons meets Where the Mountain Meets the Moon!"--